Factors Affecting the Quality of Life in Children with Epilepsy - Arthittaya Kaenkrai (2022)
Health-related quality of life (HRQOL) is considered as an important clinical outcome, especially in children with chronic illnesses. This predictive, descriptive study aimed at investigating the factors affecting health-related quality of life in children with epilepsy, including epilepsy severity, comorbidity, and family functioning. The sample, which consisted of 90 caregivers of children with epilepsy between the ages of 4 to 15 years, was recruited from the pediatric neurological out-patient clinic and in-patient wards at Prasat Neurological Institute, and Ramathibodi Hospital located in Bangkok, Thailand. Data were collected during June-August 2019. A set of questionnaires was used including demographic characteristics and medical record of illness data of children with epilepsy, the Chulalongkorn Family Inventory (CFI), and the Quality of Life in Childhood Epilepsy (QOLCE-16). Data analysis used descriptive statistics, Pearson’s product-moment correlation coefficient, and multiple regression analysis. The findings revealed that epilepsy severity, comorbidity, and family functioning could jointly predict the overall QOLCE, and accounted for 28.40% of the variance in the overall quality of life of children with epilepsy. Results of this study would help nurses and healthcare professionals provide adequate support and further design the intervention to improve the quality of life among children with epilepsy.